Exploring the wound healing potential of dietary nitrate in diabetic rat model - Hu, Xiaodan; Xu, Haoyue; Bu, Lingxue; Sun, Jian; Deng, Jiangzhi; Song, Kai; Wang, Lin; Pang, Baoxing (Frontiers in Physiology, 2024)
IntroductionThe wound healing in diabetes is hindered and prolonged due to long-term inflammation, oxidative stress damage, and angiogenesis disorders induced by high glucose status. The management of such difficult-to-treat wounds continues to pose a significant challenge in clinical treatment. Dietary nitrate, commonly found in greens such as beets and spinach, acts as a nutritional supplement and is metabolized in the body through the salivary nitrate-nitrite-NO pathway. This pathway plays a crucial role in various physiological functions, including enhancing blood flow and attenuating inflammation.MethodsIn this study, we established a diabetic rat wound model. Forty-eight rats were randomly divided into six groups (n = 8): the Con group, the Con + Nitrate group, the STZ group, the STZ + NaCl group, the STZ + rhEGF group, and the STZ + Nitrate group. Skin wound healing was assessed on the day of surgery and on postoperative days 3, 7, 10, and 14. Specimens were taken on days 7 and 14 post-surgery for relevant tests.ResultsWe found that dietary nitrate could accelerate skin wound healing by promoting angiogenesis and increasing blood perfusion. Significantly, dietary nitrate also regulated glucose and lipid metabolism and exhibited anti-inflammatory and antioxidant properties.DiscussionThese findings provide a novel theoretical basis for managing wounds in diabetic individuals, indicating the broad potential of dietary nitrate in future clinical applications.